The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1467-9620.2006.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Semilingualism Applied to the Literacy Behaviors of Spanish-Speaking Emerging Bilinguals: Bi-illiteracy or Emerging Biliteracy?

Abstract: Language differences in the United States are largely viewed as problems that schools must remedy. This paradigm has created the pervasive belief that Spanish is a root cause of underachievement for Spanish-speaking English language learners (ELLs). This article examines teacher beliefs systems with regard to the above paradigm. It also examines informal writing assessments as tools to evaluate children's bilingual writing development. Fourth- and fifth-grade students were given writing prompts in English and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 9 publications
4
69
1
Order By: Relevance
“…The underlying assumption of this practice is that bilingual students demonstrate equal competencies in both languages since bilinguals' languages develop as parallel monolinguals of each language. However, we concur with others (Baker, 2011;Escamilla, 2006;García, 2009) when they affirm that this is an inequitable practice that does not adequately display the complex language practices and proficiencies of emergent bilinguals. As Baker (2011) states, norm-referenced tests often reflect the language style and culture of White, middle-class Anglo test writers.…”
Section: Issues In the Assessment Of Emergent Bilingualssupporting
confidence: 84%
See 1 more Smart Citation
“…The underlying assumption of this practice is that bilingual students demonstrate equal competencies in both languages since bilinguals' languages develop as parallel monolinguals of each language. However, we concur with others (Baker, 2011;Escamilla, 2006;García, 2009) when they affirm that this is an inequitable practice that does not adequately display the complex language practices and proficiencies of emergent bilinguals. As Baker (2011) states, norm-referenced tests often reflect the language style and culture of White, middle-class Anglo test writers.…”
Section: Issues In the Assessment Of Emergent Bilingualssupporting
confidence: 84%
“…The lack of specific assessments created for emergent bilinguals provide teachers, districts, and departments of education with only a partial and often inaccurate view of the students' literacy growth as they develop proficiency in two languages (Escamilla, 2006;Gathercole, 2013aGathercole, , 2013b. Tests developed for native English speakers are in fact language proficiency tests when used with non-native English speakers or bilingual students, therefore doing little in the way of measuring content knowledge (Menken, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Based on survey data from 417 college programs providing bachelor's-and master's-level teacher certification across the United States, Menken and Antúnez (2001) found that when coursework in linguistics was required, it was often a survey course that provided inadequate preparation for teaching bilingual students. In-service support has also been found to be inadequate: Escamilla (2006) interviewed 12 bilingual 4th and 5th grade teachers, who reported that none of their teacher training classes was conducted in Spanish and few ongoing professional development opportunities were made available to them as teachers. The teachers also believed they were underprepared to teach writing in both English and Spanish.…”
Section: Opportunity To Learnmentioning
confidence: 99%
“…Given this scenario, of exceptional concern is the finding that language differences among ELL students are regularly perceived not as assets (e.g., the foundation for bilingualism), but as problems that schools must remedy (Escamilla, 2006;MacSwan, Rolstad, & Glass, 2002). In fact, this belief is so pervasive among teachers and policymakers that some school districts have begun to refer to these students as semilinguals (Escamilla).…”
mentioning
confidence: 99%
“…In fact, this belief is so pervasive among teachers and policymakers that some school districts have begun to refer to these students as semilinguals (Escamilla). This socially constructed concept is largely based on the widely held perception that the great majority of ELL students (especially Spanish-speaking ELL students) have little or no literacy in either their first or second language (Escamilla;Valadez, MacSwan, & Martinez, 2001). Some argue that such ELL students are unlikely to benefit from ongoing native language support and that their English literacy must be developed beginning with the assumption of a tabula rasa.…”
mentioning
confidence: 99%